2006
DOI: 10.1175/jam2395.1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Characteristics of Snowstorms in the Contiguous United States

Abstract: A climatological analysis of snowstorms across the contiguous United States, based on data from 1222 weather stations with data during 1901–2001, defined the spatial and temporal features. The average annual incidence of events creating 15.2 cm or more in 1 or 2 days, which are termed as snowstorms, exhibits great spatial variability. The pattern is latitudinal across most of the eastern half of the United States, averaging 0.1 storm (1 storm per 10 years) in the Deep South, increasing to 2 storms along the Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…By March, precipitation tends to be substantially higher, given the larger moisture holding capacity of warmer air and greater climatological ascent in the atmospheric column; events in March often either occur as heavy snowstorms or rain/mixed precipitation events due to higher temperatures. Reflecting this seasonal pattern, Changnon et al (2006) found that the greatest number of Wisconsin snowstorms was observed in March. By the late 21st century, especially under the A2 scenario, the secondary snowfall peak in March becomes much less distinct (Figure 9a), as March precipitation events become much more likely to fall in the form of rain.…”
Section: State-averaged Snow Projectionsmentioning
confidence: 95%
“…By March, precipitation tends to be substantially higher, given the larger moisture holding capacity of warmer air and greater climatological ascent in the atmospheric column; events in March often either occur as heavy snowstorms or rain/mixed precipitation events due to higher temperatures. Reflecting this seasonal pattern, Changnon et al (2006) found that the greatest number of Wisconsin snowstorms was observed in March. By the late 21st century, especially under the A2 scenario, the secondary snowfall peak in March becomes much less distinct (Figure 9a), as March precipitation events become much more likely to fall in the form of rain.…”
Section: State-averaged Snow Projectionsmentioning
confidence: 95%
“…Branick (1997) utilized the National Climatic Data Center (NCDC) Storm Data publication to create a national ''climatology'' of winter-weather events, including snow and freezing precipitation, to characterize the frequency, areal coverage, and seasonal behavior of such events. Changnon et al (2006) established a climatology of snowstorms that is based on station data from across the continental United States, and Changnon et al (2008) connected the snowstorm climatology to a climatology of surface cyclone tracks east of the Rocky Mountains. Hirsch et al (2001) more narrowly focused on a climatology of East Coast winter storms, whereas Market et al (2002) narrowed the focus to thundersnow events.…”
Section: Introductionmentioning
confidence: 99%
“…Strong snowfalls often cause damages to pasturage and other properties and bring hazardous conditions to transportation and other human activities. Therefore, numerous studies have been conducted to understand the formation, mechanisms and predictability of snowstorms (Wang and Ding 1995;Zielinski 2002;Zhang et al 2002;Kocin and Uccellini 2004;Changnon et al 2006;Sun et al 2010). Anomalous atmospheric circulation both in the troposphere and stratosphere is associated with the snowstorm and cold surge in East Asia (Sun et al 2009;Jeong et al 2006).…”
Section: Introductionmentioning
confidence: 99%